Análisis financieros y su influencia toma de decisiones gerenciales de la constructora Celso, año 2022 - Macedo Reategui, Gloria Erica (2023)
The purpose of this study was to determine how financial analysis affected the managerial choices made within the organization of Constructora Celso, in 2022, carrying out a descriptive study with a non-experimental design using the operating records of the Constructora Celso company as a sample. According to the results, real estate, machinery and equipment are the most crucial long-term investments this year. 2022 had a process of total increase due to being in a process of continuous improvement, it was dedicated to the acquisition of machinery and equipment and in its desire to have a modern infrastructure, it made the following decisions made by the owners and they were: financial diagnosis, financial evaluation, financial selection and financial execution. The financial decision they chose was to make money grow and have a good heritage in the future, that is, to invest and to put it to work, for this the money should preferably be in a banking institution, to obtain future profits. Internal financing refers to funds produced by the company itself, profits realized but not distributed, or funds contributed by its partners. These funds are made up of reserves, amortizations and provisions, which mainly represent the value of the assets contributed by the partners together with the benefits produced by the activity, economic result of the year.